2021
DOI: 10.3389/fenvs.2021.744781
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Relationship Between Economic Complexity and Environmental Degradation: Evidence From Top Seven Economic Complexity Countries

Abstract: The continuous growth in CO2 emissions of nations around the globe has made achieving the aim of sustainable development extremely challenging. Therefore, the current research assesses the connection between CO2 emissions and economic complexity in the top 7 economic complexity countries while taking into account the role of economic growth, renewable energy consumption, and globalization for the period between 1993 and 2018. The research aims to answer the following questions: 1) What is the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 66 publications
3
5
0
1
Order By: Relevance
“…BRI countries, as part of a global network, can work together on climate agreements and conservation efforts, sharing knowledge and resources to reduce ecological footprints collectively [ 28 ]. The findings of the study have similar findings to those of earlier studies [ 16 , 22 , 31 33 , 45 , 46 ]…”
Section: Empirical Findings and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…BRI countries, as part of a global network, can work together on climate agreements and conservation efforts, sharing knowledge and resources to reduce ecological footprints collectively [ 28 ]. The findings of the study have similar findings to those of earlier studies [ 16 , 22 , 31 33 , 45 , 46 ]…”
Section: Empirical Findings and Discussionsupporting
confidence: 91%
“…Economic reforms are involved in adopting practices that meet present economic needs while ensuring the long-term viability of natural resources and ecosystems [ 63 ]. Reforms such as investing in renewable energy, promoting energy efficiency, and implementing sustainable agricultural practices can all contribute to reducing the ecological footprint [ 46 ]. These reforms may improve the efficiency of resource use in sectors such as manufacturing, transportation, and construction, less waste is generated, and fewer resources are consumed [ 6 ].…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary [ 89 ], revealed that ECI raises CO 2 levels in the United States. Similarly [ 90 ], proposed that CO 2 emissions rise when ECI increases in the seven countries with the greatest ECI. Furthermore [ 7 ], shown that collective economic complication reduces environmental degradation in India.…”
Section: Resultsmentioning
confidence: 99%
“…‫المخصص‬ ‫التمويل‬ ‫وينخفض‬ ‫البيئي،‬ ‫الوعي‬ ‫ينخفض‬ ‫االقتصادي‬ ‫النمو‬ ‫بداية‬ ‫في‬ ‫أنه‬ ‫بسبب‬ ‫ذلك‬ ‫ويرجع‬ ‫الرغبة‬ ‫المجتمعات‬ ‫لدى‬ ‫سيكون‬ ‫الناتج‬ ‫يادة‬ ‫ز‬ ‫مع‬ ‫لكن‬ ‫البيئي،‬ ‫التلوث‬ ‫لمنع‬ ‫المتقدمة‬ ‫التقنيات‬ ‫افر‬ ‫يتو‬ ‫ال‬ ‫و‬ ‫البيئة،‬ ‫لحماية‬ ‫تكاليف‬ ‫دفع‬ ‫على‬ ‫ة‬ ‫القدر‬ ‫و‬ ‫للبيئة‬ ‫صديق‬ ‫اإلنتاج‬ ‫نحو‬ ‫التحرك‬ ‫و‬ ‫اإلنتاج‬ ‫تقنيات‬ ‫وتحسين‬ ‫البيئة،‬ ‫حماية‬(Martins, et al, 2021) …”
unclassified